2011
DOI: 10.1056/nejmoa1012740
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Use of Tissue Plasminogen Activator and DNase in Pleural Infection

Abstract: Intrapleural t-PA-DNase therapy improved fluid drainage in patients with pleural infection and reduced the frequency of surgical referral and the duration of the hospital stay. Treatment with DNase alone or t-PA alone was ineffective. (Funded by an unrestricted educational grant to the University of Oxford from Roche UK and by others; Current Controlled Trials number, ISRCTN57454527.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
756
5
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 675 publications
(826 citation statements)
references
References 46 publications
25
756
5
14
Order By: Relevance
“…Several reviews have concluded that IPFT appears to decrease the requirement for surgical interventions but does not decrease mortality in adults 8, 9. Although early studies in people identified improved survival after IPFT,10, 11, 12 2 of the largest randomized, placebo‐controlled studies in adults failed to show a positive effect with IPFT without concurrent intrapleural administration of DNase 13, 14. This discrepancy has been attributed to wide variation in patient selection, dosage regimens, and type of fibrinolytic agent used (including urokinase, streptokinase, alphadornase, and rTPA).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reviews have concluded that IPFT appears to decrease the requirement for surgical interventions but does not decrease mortality in adults 8, 9. Although early studies in people identified improved survival after IPFT,10, 11, 12 2 of the largest randomized, placebo‐controlled studies in adults failed to show a positive effect with IPFT without concurrent intrapleural administration of DNase 13, 14. This discrepancy has been attributed to wide variation in patient selection, dosage regimens, and type of fibrinolytic agent used (including urokinase, streptokinase, alphadornase, and rTPA).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, doses from 2–100 mg of alteplase have been used with variable success 11. Dwell times have varied from 1 to 24 hours and frequency of administration from 1 to 3 times daily 10, 11, 14, 19. For rTPA to be effective, endogenous plasminogen must be available for conversion into plasmin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations